2023
DOI: 10.3390/buildings13081913
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Spatial Pattern of Traditional Villages from the Perspective of Courtyard House Distribution

Abstract: As clan and blood relations are the essential core of rural social attributes, the rise and fall of the main family names in a village not only affects the spatial arrangement of their internal courtyard houses but also influences the overall spatial pattern of the village. Taking Pei Cheng Village as an example, in this study, quantitative analyses, such as those entailing standard deviation ellipse, kernel density, and space syntax, are incorporated to investigate the changes in rural family names’ courtyard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Secondly, a low-density, strong, recognizable rural spatial form can protect the ecological environment and local culture while enhancing the visual experience of tourists and rural tourism. For example, studies on famous tourist villages, including 57 tourist villages in Fujian Province [13], Longchuan Village in Anhui Province [14], and Luxiang Village and Mingyuewan Village in Jiangsu Province [15], have found that the sustainable development of villages, especially traditional villages, cannot be separated from the protection of their original and iconic spatial form. It is essential to summarize the regional laws regarding the characteristics of the rural spatial form.…”
Section: Literature Review 121 Research On the Interaction Between Ru...mentioning
confidence: 99%
“…Secondly, a low-density, strong, recognizable rural spatial form can protect the ecological environment and local culture while enhancing the visual experience of tourists and rural tourism. For example, studies on famous tourist villages, including 57 tourist villages in Fujian Province [13], Longchuan Village in Anhui Province [14], and Luxiang Village and Mingyuewan Village in Jiangsu Province [15], have found that the sustainable development of villages, especially traditional villages, cannot be separated from the protection of their original and iconic spatial form. It is essential to summarize the regional laws regarding the characteristics of the rural spatial form.…”
Section: Literature Review 121 Research On the Interaction Between Ru...mentioning
confidence: 99%
“…In Xuzhou's traditional architecture, the courtyard house and three-sided courtyard are the primary building forms. The typical floor plan is a "one bright, two dark" layout with three bays [40]. Wooden partitions are commonly used indoors, with single doors for each partition.…”
Section: Residential Layout 331 Formmentioning
confidence: 99%
“…In Xuzhou's traditional architecture, the courtya are the primary building forms. The typical floor pla with three bays [40]. Wooden partitions are commo for each partition.…”
Section: Formmentioning
confidence: 99%
“…This refers to the clear and stable living level and spatial structure of the settlement formed after a long period of precipitation on the natural basis of a specific region. The public spaces of traditional villages, as an indispensable part of the material carrier, connect and link the households in the villages and play an important role in the overall stability of the villages [15]. However, the steep decline in the total number of natural villages [16] indicates a rapid and irreversible decline of village extinction in China.…”
Section: Introductionmentioning
confidence: 99%